2000
DOI: 10.1007/s002560000243
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted imaging of the musculoskeletal system in humans

Abstract: This article reviews the principles of diffusion-weighted imaging (DWI) and recent results in DWI of the musculoskeletal system. The potential of DWI in the diagnosis of pathology of the musculoskeletal system is discussed. DWI is a relatively new MR imaging technique that has already been established in neuroradiology, especially in the early detection of brain ischemia. The random motion of water protons on a molecular basis can be measured with DWI. To date DWI of the abdomen and of the musculoskeletal syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
82
2
3

Year Published

2002
2002
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(91 citation statements)
references
References 36 publications
4
82
2
3
Order By: Relevance
“…Commonly, malignant tumors demonstrate nuclear contour deformation, enlarged nuclei, and hyperchromatism, while also showing a high cellularity. As a result, the extracellular diffusion space of water molecules reduces and the ADC value of malignant tumors decreases (12,19,23). Moreover, it was demonstrated that the property of the extracellular matrix contributed to diffusion restrictions in these tumors (12).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Commonly, malignant tumors demonstrate nuclear contour deformation, enlarged nuclei, and hyperchromatism, while also showing a high cellularity. As a result, the extracellular diffusion space of water molecules reduces and the ADC value of malignant tumors decreases (12,19,23). Moreover, it was demonstrated that the property of the extracellular matrix contributed to diffusion restrictions in these tumors (12).…”
Section: Discussionmentioning
confidence: 99%
“…The most important component of signal attenuation on DWI in tumor tissues is the diffusion of water molecules in the extracellular spaces (12). Commonly, malignant tumors demonstrate nuclear contour deformation, enlarged nuclei, and hyperchromatism, while also showing a high cellularity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diffusion-weighted imaging (DWI) can quantitatively assess the mobility of water molecules by allowing calculation of the apparent diffusion coefficient (ADC) [22]. Extracellular motion of free water is the main contributor to the ADC and signal loss in tissues [23,24].…”
Section: Fat and Water Contentmentioning
confidence: 99%